The Implementation Of Teaching English For Young Learners At The Third Grade Of Sdn 018 Samarinda In The 2012/2013 Academic Years - Denok Marlisa Dewi (Prodi Ilmu Administrasi Negara, 2016)
ABSTRACTThis study focused on the implementation of teaching English for young learners at the third grade. Implementation means application process of idea, concept, and policy or innovation in practical act that gave impact and also change in knowledge, skill, value, and attitude (Kunandar, 2007-233). The purposes of this study are intended to find out the implementation English teacher teach English for young learners and the problems faced by the teacher in the process of teaching and learning English for young learners of SDN 018 Samarinda. The researcher conducted the observation for three meetings in the third grade of SDN 018 Samarinda. The researcher used steps in collecting data: (1) Doing the observation by using the teacher observation form as a guide, and (2) Conducting the interview to the teacher. To analyze the data, the researcher consist of three concurrent flows of activity in the model: data reduction, data display, and data conclusion drawing/verification.The result in terms of implementation of teaching and learning process, the teacher has different way and result in observation. The results of teaching and learning depend on teacher’ process of ides, concept, policy or innovation, knowledge, skill, value and attitude in the way of teaching method and the problems faced by the teacher teaching English for young learners were 1) Facility for English teaching. 2) The large number of the students in the classroom in doing the exercise. 3) The students' parents who do not support their children in learning English.